Evaluation of Hydroalcoholic Extract of Avicennia marina Effect on Viability and Expression of Genes Involved in the Apoptotic Pathway of Glioblastoma Cancer Cell Line: Biological Studies on hydroalcoholic extract of Avicennia marina - Navid Ahmadi Nasab,; Masoumeh Keshavarz,; Masoumeh Keshavarz, (Iranian Journal of Pharmaceutical Sciences, 2022)
Avicennia marina is known as the main species of mangrove forests in Iran. The study of biological processes shows that the presence of a wide range of phytochemical compounds in this plant has made it an excellent candidate for use in therapeutic applications. The purpose of this study was to investigate the cytotoxicity and apoptosis induction of hydroalcoholic extract of A. marina on human glioblastoma and normal fibroblast cell lines. With this aim, the hydroalcoholic extract of A. marina leaves were extracted firstly and then the target cells were treated with different concentrations of the extract. Cell viability percentage of treated normal and cancer cells was assessed using MTT assay at 24, 48 and 72 h. Also, the half maximal inhibitory concentration (IC50) values of hydroalcoholic extract were calculated at the times of testing for both cancer and normal cell lines. Quantitative PCR (qPCR) was used to evaluate the expression of Bcl2 and Bax apoptotic genes and dual staining (AO / EB) was used to stain the nucleus of target cells for imaging by a fluorescence microscope. The results of cytotoxicity tests showed that the hydroalcoholic extract of A. marina is able to inhibit the metabolic growth of more than half of U-87 MG cells at a concentration of 0.57 mg/ml. It was also found that hydroalcoholic extract has a higher effectiveness in inhibition of cancer cells proliferation compared to normal cells. Analysis of Bcl-2 and Bax genes expression levels in cells treated with A. marina extract showed a significant decrease in Bcl-2 anti-apoptotic gene expression levels (P <0.01) and an increase in Bax apoptotic gene expression levels (P <0.001). Eventually, the results of the dual staining study of the cell nucleus clearly depicted the morphological changes in different stages of apoptosis and confirmed the results of the qPCR and MTT assay.